Communication in the Age of Disinformation – The growth of the far-right and digital illiteracy - Jerónimo, Joana (2024)
In a context of growing support for the far right in Portugal, this article examines the interplay between this phenomenon and the digital illiteracy of the population. Highlighting the role of social media and online platforms in the spread of extremist ideologies, it argues that the lack of digital skills makes citizens vulnerable to manipulation and the dissemination of propaganda. By advocating for the importance of promoting digital literacy as a vital strategy to combat the rise of the far right, the article urges readers to consider the role of digital education in building a society more resilient to political polarization and committed to democratic values.